C. S. Lewis : the artist as educator - Brady, Rosalyn (Trinity College (Dublin, Ireland). School of Education, 2001)
C.S. Lewis has received the critical attention primarily of theologians and literary critics who have focused on his work as a scholar, critic, novelist and apologist. This thesis offers a new focus for his writings. It examines biographical details of his life and the educational ideas and beliefs implicit in his work with a view to demonstrating the manner in which they comprehend and unify Lewis’s fundamental impulses as artist and educator. The study suggests that if Lewis’s vision of and for education is established through a philosophic explication of the entire Lewis oeuvre, if his pedagogic practices are established, if the educational implications of his theory of imagination and myth are explored, and if all are placed within the framework o f his religious beliefs, then a deeper understanding of Lewis’s writings and ideologies will emerge.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin